Specialist Disability Accommodation in the social housing sector: Policy and practice - Crowe, Adam; James, Amity; Peaty, Gwyneth; Malbon, Eleanor; Ellis, Katie (Australian Housing and Urban Research Institute, 2024)
An objective assessment of reports published in the AHURI journal series by carefully selected experts in the field ensures that material published is of the highest quality. The AHURI journal series employs a double-blind peer review of the full report, where anonymity is strictly observed between authors and referees.